Bringing technological innovations to African smallholder farmers through intellectual property and technology transfer management: The AATF approach - Boadi, R.Y.; Bokanga, M. (TSAP and ILRI, 2006)
Yields of the major staple crops (maize, sorghum, millet, cassava, cowpea and bananas/plantains) of smallholder farmers in Africa have remained stagnant or even declined in the past 40 years. Numerous biotic and abiotic stresses facing these crops in Africa have contributed to this scenario. Local research efforts to overcome these stresses are hampered by declining support for agricultural research, limited access to elite genetic material and other technologies protected by intellectual property rights and absence of commercial interest in these crops by private owners of agricultural technologies. This paper addresses the intellectual property issues (IP) and partnership arrangements associated with the access, development and deployment of agricultural technologies targeting smallholder farmers in sub-Saharan Africa as addressed by the African Agricultural Technology Foundation (AATF). AATF is a new initiative addressing these challenges by negotiating access to proprietary technologies and facilitating their conversion into technological solutions deliverable to smallholder farmers in sub-Saharan Africa.